2009
DOI: 10.6026/97320630004248
|View full text |Cite
|
Sign up to set email alerts
|

LCK, survivin and PI-3K in the molecular biomarker profiling of oral lichen planus and oral squamous cell carcinoma

Abstract: T cell signaling is critical in oral lichen planus (OLP) based on the pathogenesis of this chronic inflammatory autoimmune mucocutaneous lesion. Lck plays a key role in T cell signaling; ultimately this signaling affects other targets such as PI-3K. Excessive activity in PI-3K inhibits apoptosis and promotes uncontrolled cell growth. Molecular biomarker profiling in OLP, Chronic Interface Mucosities (CIM), Epithelial Dysplasia (EpD) and Oral Squamous Cell Carcinoma (SCCA) with application of the principle of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
25
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 32 publications
4
25
0
1
Order By: Relevance
“…Similar arguments stand for the increase rate of cancer transformation from the two distinct forms of OPM, epithelial dysplasia (EpD) and erythroplakia, compared to leukoplakia [19]. A case in point pertains to our data, which showed that OPM cases of EpD revealed similar molecular signatures with OSCC cases [10]. …”
Section: Methodssupporting
confidence: 77%
See 3 more Smart Citations
“…Similar arguments stand for the increase rate of cancer transformation from the two distinct forms of OPM, epithelial dysplasia (EpD) and erythroplakia, compared to leukoplakia [19]. A case in point pertains to our data, which showed that OPM cases of EpD revealed similar molecular signatures with OSCC cases [10]. …”
Section: Methodssupporting
confidence: 77%
“…Molecular proteomic profiling, such as our work [10], further indicates that OLP, OPM, OSCC and other oral and pharyngeal cancers may benefit from therapy based on inhibitors of PI-3k, Lck, and related signaling pathways, used as single or multi-drug therapy. It is our contention here that a principal mode of action of these interventions is to target specific events modulated by T cells subpopulations, and driven by the microenvironment, such as, for instance, the use of anti-Lck to control inflammation, cancer progression and metastasis, or the use of PI-3k inhibitors in modulating the microenvironment to subdue tumor transformation and proliferation in oral premalignant lesions such as epithelial dysplasia.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…However, these studies were in most cases dealing with one single gene or with a single gene family. [36][37][38][39][40][41][42][43][44] However, only few of them have a high number of interactions with the other genes in the network and therefore they may play a major role. These genes were identified and termed as ""leader genes"".…”
Section: Genes Network Involved In Olp Pathogenesismentioning
confidence: 99%